Die Ursprünglichkeit der brasilianischen Campos Cerrados und neue Beobachtungen an ihrer Südgrenze - Hueck, Kurt (ERDKUNDE, 1957)
In botanical and geographical literature on Brazil the vegetation of the Campos Cerrados in the interior of the country is frequently referred to as a secondary formation due to human interference, in particular resulting from burning. This paper communicates the data which make it likely that the concept regarding the artificial origin of the Campos Cerrados is wrong. In the opinion of the author the Campos Cerrados are completely natural plant associations.